Analysis of malignancy predictors for follicular thyroid tumors - Zorić, Goran V.; Nikolić-Djurović, Marina M.; Paunović, Ivan R.; Diklić, Aleksandar D.; Bukumirić, Zoran M.; Slijepčević, Nikola A.; Taušanović, Katarina M.; Odalović, Božidar A.; Jovanović, Milan D.; Živaljević, Vladan R. (Vojnosanitetski pregled, 2021)
Background/Aim. Establishing a preoperative diagnosis of thyroid follicular tumors is difficult due to the fact that the cell morphology of adenomas and carcinomas are similar and that capsular and vascular invasion cannot be determined by cytology. We analyzed predictive factors of follicular carcinoma in order to enable a surgeon to indicate operative treatment and to perform an adequate operation for each patient with a follicular neoplasm. Methods. In this retrospective study, we analyzed medical records of all patients with follicular thyroid tumors operated at an endocrine surgery unit of a tertiary referral academic hospital, between 2008 and 2012. A total of 263 operated patients were included and divided into follicular adenomas (n = 97) and follicular carcinomas (n = 166) based on the histopathology results. The most important demographic and clinical characteristics were analyzed by univariate and multivariate logistic regression analysis. Results. In adenoma group (19 males, 78 females) age range was 19–79, mean age 50. In carcinoma group (35 males, 131 females) age range was 15–78, mean age 48. Univariate analysis showed that thyroglobulin concentration ≥ 500 ng/mL, tumor diameter < 30 mm, presence of more than one thyroid nodule and an afunctional/hypofunctional nodule were significantly more frequent in follicular carcinoma than in follicular adenoma. Independent predictive factors of malignancy were: elevated preoperative thyroglobulin concentration (≥ 500 ng/mL) and presence of more than one nodule. Based on our results we formed a nomogram, a two-dimensional diagram designed to enable estimation of preoperative probability of malignancy. Conclusion. Elevated preoperative thyroglobulin concentration, ≥ 500 ng/mL, and the presence of more than one nodule are independent predictors of malignancy for follicular thyroid carcinomas.